Innovative Process Development Trend in the Publishing and Printing Industry - Kotlyarevsky, Ya.V.; Kniaziev, S.I.; Melnikov, O.V. (Science and Innovation, 2024)
Innovative development of publishing and printing industry in the context of global trends has been studied. The organizational and economic relations arising due to the innovation-based development of publishing and printing industry have been described; their impact on the prospects for the national economy growth have been assessed.